PROFIL TINGKATAN HABITS OF MIND DAN KECEMASAN KOGNITIF DALAM MATA PELAJARAN BIOLOGI PADA SISWA SMA DI KOTA BANDUNG - Ilma Riksa Isfiani (Biodidaktika : Jurnal Biologi dan Pembelajarannya, 2016)
This research aims to explore level of habits of minds and cognitive anxiousness profile of senior high school students in Bandung. Descriptive analysis is used as a research method with stratified random sampling techniques. The population of this research were all of the students 11th and 12th grade in Bandung. Collecting data was conducted on 11th and 12th grade of four different school as sample using questionnaire instrument. Habits of mind instrument was adapted from Costa and Kallick’s and anxiousness cognitive test was adapted from Cassady and Johnson’s. The result of this research shows that habits of minds score average and cognitive anxiousness score average of 11th and 12th grade were 111,77 (75%) and 53,15 (66%) for 11th grade and 114,66 (76%) and 56,17 (69%) for 12th grade. The results show us that habits of minds and cognitive anxiousness of  11th and 12th grade were moderate categorically.